Analysis of Secondary School Infrastructure Distributions in Osogbo Metropolis, Nigeria - OLAYIWOLA, OLAYODE; Sunday, Ogundahunsi Dele; Binde, Gasu Martins; Babatunde, Adedotun Samuel Babatunde; Christiana, Olayode (Ruang, 2024)
This study analysed the geospatial distribution of secondary schools infrastructure in the Osogbo metropolis, Nigeria, with a focus on evaluating accessibility and spatial patterns of school locations. By examining the spatial distribution, travel distances, and clustering of schools, this research offers a novel contribution to the educational planning literature. The data were collected through both primary and secondary sources, utilizing total enumeration for spatial data and a sampling frame of 17,595 students and 452 teachers across 120 public and private secondary schools. Using a balloting approach, at 15%, 19 schools were sampled, followed by a random sampling technique to choose 5% of students and staff, resulting in a total of 906 respondents (880 students and 26 teachers). The analysis, employing Moran's I Index, revealed a value of 0.75 and a p-value of 0.14, indicating a random distribution of schools with a z-score of 1.45, falling within the expected range. The average distance traveled to schools was 1.582 km, reflecting spatial inequities in accessibility. This study provides critical insights for policymakers, emphasizing the need for both public and private stakeholders to ensure equitable distribution and accessibility of secondary schools across Osogbo metropolis.